Implementasi Kebijakan Kartu Identitas Anak (KIA) Sebagai Upaya Pemenuhan Hak Anak Di Kabupaten Mojokerto - Al Annisa Nuraini Riskhoh Saputri; Anggraeny Puspaningtyas; M. Kendry Widiyanto (Lembaga Pengembangan Kinerja Dosen, 2024)
The study looks at how the Child Identity Card (KIA) policy is implemented in Mojokerto district to protect children's rights. The focus of the research is the importance of protecting children's rights through KIA. The aim of the study is to find patterns and important results related to the implementation of KIA in the region. In order to study the implementation of KIA in the Population and Civil Records Department of Mojokerto district, the study used a qualitative approach to the design of case studies. This research helps to enhance the realization of children's rights through good policies, especially in terms of socializing the rights of children to society. It is hoped that this research will provide a better insight into the importance of public policies affecting the right of children to protect them.